Corruption in Indonesia: The Dominance of structural factors in the formation of a culture of corruption - Nugroho, FEBRIANTO Andi (Maliki Interdisciplinary Journal, 2026)
Corruption in Indonesia is commonly explained through two major perspectives: cultural factors and structural factors. This article aims to examine the dominant factor in the formation of corruptive culture by emphasizing structural conditions as the primary explanatory variable. The study employs a qualitative approach based on document analysis and secondary data obtained from reports of the Corruption Eradication Commission (KPK), Statistics Indonesia (BPS), Transparency International, and relevant academic literature. The findings indicate that weak oversight mechanisms, imbalanced institutional incentives, and inconsistent law enforcement are the key structural factors that create opportunities and motivations for corrupt behavior. The study argues that corruptive culture should be understood as a consequence of repeated corrupt practices within a weak institutional system rather than as the principal cause of corruption itself. Evidence further demonstrates that structural reforms, including strengthening supervisory institutions, improving transparency through e-government, and enhancing public governance, are more effective in reducing corruption than approaches focused solely on moral education and cultural change. Therefore, institutional reform should be prioritized as the most effective strategy for combating corruption and fostering long-term integrity in Indonesia.